Characterization of the immune cell infiltration landscape in myxofibrosarcoma to aid immunotherapy - Zhao, Zi-Yue; Chen, Zhuo-Yuan; Yu, Bin; Xiao, Bo; Liu, Li-Yan; Xia, Yu; Li, Ao-Yu; Wang, Ping-Xiao; Xiang, Cheng; Liu, Chao; Yang, Hui-Qin; Li, Hui; et al. (Frontiers in Immunology, 2022)
Myxofibrosarcoma (MFS) is a highly malignant subtype of soft tissue sarcoma, accounting for 5% of cases. Immunotherapy guided by immune cell infiltration (ICI) is reportedly a promising treatment strategy. Here, MFS samples (n = 104) from two independent databases were classified as ICI clusters A/B/C and gene clusters A/B/C. Then, a close relationship between ICI and gene clusters was established. We found that the features of these clusters were consistent with the characteristics of immune-inflamed tumors (cluster C), immune-desert tumors (cluster B), and immune-excluded tumors (cluster A). Moreover, cluster C was sensitive to immunotherapy. Finally, an independent ICI score was established to predict the therapeutic effect, which has prospects for application in guiding immunotherapy during clinical practice.